Homeopatia e espiritualidade: uma revisão integrativa - Cláudio Eduardo Falcão Dias (2019)
Introduction: Although there are many studies on the use of homeopathy and spiritual therapies, both considered members of the Integrative and Complementary Practices (PICs), there are few studies that seek to understand a possible similar modus operandi generating positive influences in improving the overall health to human being. Objective: This research has the general objective to accomplish an integrative review of the literature on the content involving homeopathy and Spiritual Therapies and the existence of similar positive influences in relation to the overall health of human beings, especially in relation to mental health. Methods: an integrative review of the literature was performed, analyzing a possible similar form of action between homeopathy and spiritual therapies in the integral health of the human being. To do this, we searched the databases: VHL, Cochrane Library, PsycInfo, PubMed, Scopus and Web of Science. Scientific articles were searched from any language, year and place of publication. The entire process was carried out jointly by two previously trained evaluators. Results: Of the 1,282 studies found resulting from the search in the databases, 252 were in duplicity. After the selection and reading of the title and summary of the remaining 1,026 articles, within the eligibility criteria, resulted in 13 articles that were analyzed in full. Discussion: Few studies have investigated the possible similar mechanisms that have been used by Homeopathy and Spiritual Therapies. It was verified that Homeopathy and Spiritual Therapies analyzed have contributed to the improvement of both mental health and the integral health of the individuals who use these therapies. There is a use of mental health interventions and a broader view of the health and disease process by both therapies. Conclusions: The results of this integrative literature review allow us to conclude that both homeopathy and spirituality have positive influences on the integral health of the human being. Both practices often use common interventions in the healing process in the area of mental, psychic and / or emotional health, promoting better coping skills in relation to suffering in its various modalities, as well as increasing resilience in life. clinical situations presented by the patients. The positive influences found may be related to a similar perception used by both homeopathy and spirituality, regarding the process of human illness, addressing not only the biological aspects, but also the functional, social and spiritual aspects. Further studies are needed to better understand the possible common mechanisms used by these practices to improve people's health conditions.